2022
DOI: 10.3389/fmars.2022.968470
|View full text |Cite
|
Sign up to set email alerts
|

Bioregionalization of the coastal and open oceans of British Columbia and Southeast Alaska based on Sentinel-3A satellite-derived phytoplankton seasonality

Abstract: Classifying the ocean into regions with distinct biogeochemical or physical properties may enhance our interpretation of ocean processes. High-resolution satellite-derived products provide valuable data to address this task. Notwithstanding, no regionalization at a regional scale has been attempted for the coastal and open oceans of British Columbia (BC) and Southeast Alaska (SEA), which host essential habitats for several ecologically, culturally, and commercially important species. Across this heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 124 publications
5
6
0
Order By: Relevance
“…Despite OLCI slightly overestimating lower-range Chla values (0.17 to 0.28 mg/m 3 ) in comparison to in situ measurements, the validation results demonstrate the excellent performance of the Polymer AC algorithm in this region, with dynamic ranges consistent with in situ values [50]. Our observation is supported by Giannini et al (2021) [62], who evaluated the performance of Polymer and other AC schemes in the northeast Pacific region and found that Polymer provided the best results for Chla and that the dynamic range was within the observed range [39].…”
Section: Chlorophyll-a Concentrationmentioning
confidence: 69%
See 1 more Smart Citation
“…Despite OLCI slightly overestimating lower-range Chla values (0.17 to 0.28 mg/m 3 ) in comparison to in situ measurements, the validation results demonstrate the excellent performance of the Polymer AC algorithm in this region, with dynamic ranges consistent with in situ values [50]. Our observation is supported by Giannini et al (2021) [62], who evaluated the performance of Polymer and other AC schemes in the northeast Pacific region and found that Polymer provided the best results for Chla and that the dynamic range was within the observed range [39].…”
Section: Chlorophyll-a Concentrationmentioning
confidence: 69%
“…This oceanographic region (Figure 1) is classified as an HNLC area with abundant nitrate concentrations and moderate primary productivity throughout the year due to limited iron availability [46,47]. The primary productivity in the region fluctuates annually between 5 and 18 mol C m −2 yr −1 [48], whereas the concentrations of Chla in the region exhibit no seasonal or interannual variability, with values ≤ 0.5 mg/m 3 [6,[46][47][48][49][50]. This pattern has been confirmed by remote sensing of the surface Chla and recent observations from the Biogeochemical Argo float (BGC-Argo) deployed in the SNEP, which recorded low variability in Chla concentrations of the upper ocean between 0 and 150 m [40].…”
Section: Study Areamentioning
confidence: 99%
“…From fall to winter, the upper layer is cooled by storms; while in spring and summer, calmer conditions allow the surface layer to warm up, particularly on sheltered coasts (Thomson, 1981;Suchy et al, 2022). Spring and summer runoff from the Fraser River forms a brackish layer that meets the oceanic, nitrate-charged waters of the Strait of Juan de Fuca, forming a strong vertical tidal mixing in Haro Strait (Mackas and Harrison, 1997;Li et al, 2000), generating high levels of primary productivity in springtime (Peña et al, 2016;Marchese et al, 2022;Suchy et al, 2022). Photosynthetically active radiation values range from ~5 to 60 Ein/m per day in the northern and central regions of the Salish Sea, with peaks in summer and minimum values in winter (Suchy et al, 2019).…”
Section: Study Areamentioning
confidence: 99%
“…Much of the nearshore tends to experience seasonally strong, juxtaposing air-sea CO 2 fluxes, leading to near zero net annual CO 2 fluxes (nearshore white colours in Figure 5c). For example, closer to shore north of 50 N and south of the Southeast Alaska Archipelago, winter mixed layer deepening brings water rich in nutrients and CO 2 from respired organic matter to the surface, increasing pCO 2 , leading to strong CO 2 outgassing to the atmosphere when light is limiting (supplementary Figure S12a; Marchese et al, 2022). In the spring, substantial primary productivity draws down pCO 2 (Marchese et al, 2022), reverting the region to a prominent sink for atmospheric CO 2 (supplementary Figure S12b).…”
Section: Regional Patternsmentioning
confidence: 99%